Pretzel knot compared with standard suture knots - (:unkn) unknown (SPRINGER, 2012)
Aim of this paper is to compare the biomechanical properties of the Pretzel knot with the selected arthroscopic knots and to test the mechanical safety of this knot. The hypothesis was that the Pretzel knot may have equal or better mechanical properties than the arthroscopic knots tested in this study. SMC, Giant, Dines, Nicky's, Tennessee Slider knots were chosen for comparison. Original and backed configuration of knots were prepared with no. 2 braided polyester sutures. Cyclic loading and load to failure tests were performed. Parameters tested were loop security, maximum elongation and load at failure. Number of steps needed for preparation of each knot was also recorded. One-way ANOVA for repeated measures was performed for all knots. Steps needed for preparation were 2 for Pretzel and Tennessee Slider, 3 for Nicky's, SMC and Dines and 4 for Giant. The Pretzel knot in original configuration had significantly better loop security compared to SMC, Dines, Nicky's and Tennessee knots (P = 0.01). Loads at failure were not significantly different between knots in their original configurations. Giant and Dines knots showed better maximum elongations in cyclic loading (P = 0.0059) and load to failure tests (P = 0.0001). Backing up the knots with 3-RHAPs eliminated most of these significant differences. Clinically, simplicity and safety are two important components in arthroscopic knot tying. Despite its simple configuration, Pretzel knot has some similar and increased mechanical properties compared to the tested knots that are widely used.
Keywords: Pretzel knot; Locking sliding knot; Loop security; Arthroscopic knots; ROTATOR CUFF REPAIR; ARTHROSCOPIC KNOTS; SLIP KNOT; LOCKING MECHANISM; ELONGATION; STRENGTH; FAILURE